Experimental validation of numerical structural dynamic models for metal plate joining techniques. (August 2018) - Van Belle, L; Brandolisio, D; Deckers, E; Jonckheere, S; Claeys, C; Pluymers, B; Desmet, W
Joined structures are of great industrial relevance. The dynamic effects of joints are, however, often practically difficult to accurately account for in numerical models, as they often lead to local changes in stiffness and damping. This paper discusses the comparison between measurements and simulations of joined panels considering four different joining techniques: adhesive bonding, metal inert gas welding, resistance spot welding and flow drill screwing. An experimental modal analysis is performed on the different systems and the power injection method is applied to determine the loss factors of single plate systems and their joined counterparts. The joined panels are modeled in a holistic simulation environment with particular focus on the joining region, by the application of predefined and generic joint models. A very good agreement is obtained between the simulated dynamic behavior and the experimental results, showing that an accurate representation of the joints has been obtained.